Slang jest spoko? Pedagogiczne aspekty obecności socjolektu uczniowskiego w dyskursie publicznym - Anna Dąbrowska (Problemy Wczesnej Edukacji)
Students slang as a socially conditioned variety of language was initially intended and used by teenagers exclusively for informal contacts between peers. Today, it is also used for communication between children, young people and adults, including in official situations; it is even present in public discourse. In this article I discuss the expansion of teenage slang and its consequences. I have tried to identify shifting cultural contexts as one of the contributing factors, providing examples of lexical slang elements used in media communication, and reflecting on the educational significance of the introduction of teenage language into public discourse.